Design of electromagnetic field probe system - Teo, Bertrand Wei Xuan (Nanyang Technological University, 2024)
This project involves designing a field probe system to determine the magnitude and direction of the E-field around a solenoid. This includes the driver circuits and the relevant hardware and probe designs required to measure the E-fields. The design can drive the solenoid at minimal cost and complexity. Implemented with microcontrollers, improvements through better feedback can be made without additional hardware. Probe response employs a 50dB differential amplifier to increase response and reduce noise and coupling effects.